Sport Connection Scale (ECE): Acquiescence Control and Invariance - Daniele de Campos; Maynara Priscila Pereira da Silva; Nathalia Bonugli Caurin; Rafael Moreton Alves da Rocha; Evandro Morais Peixoto (Psicologia: Teoria e Pesquisa, 2024)
Abstract The Sports Connection Scale (ECE) is one instrument to assess the connection of the 5C’s model of positive youth development. In a previous study, the scale presented a two-factor solution, despite the theory suggesting a unifactorial structure. This study aims to compare the ECE unifactorial model with and without acquiescence control to the two-factor model and to test the scale invariance between collective and individual modalities practitioners in a sample of young Brazilians. The results indicate the unifactorial solution is acceptable for the controlled model and that the instrument is not equivalent between the two groups. The adequacy of the instrument and the influence of response bias in the item's answers were verified.